Cyprinus carpio TRIF Participates in the Innate Immune Response by Inducing NF-κB and IFN Activation and Promoting Apoptosis - Liu, Rongrong; Liu, Xiaoye; Song, Meijiao; Qi, Yue; Li, Hua; Yang, Guiwen; Shan, Shijuan (Frontiers in Immunology, 2021)
Trif, an important adaptor downstream of Toll-like receptor signaling, plays a critical role in the innate immune response. In this study, the full-length coding sequence of trif from common carp (Cyprinus carpio L.) was cloned and characterized. Bioinformatics analysis showed that common carp Trif exhibited a conserved TIR domain and had the closest relationship with grass carp Trif. Expression analysis revealed trif to be constitutively expressed in the examined tissues of common carp, with the highest expression in the spleen and the lowest expression in the head kidney, and could be upregulated under Aeromonas hydrophila and poly(I:C) stimulation in vivo and under poly(I:C), LPS, PGN, flagellin and Pam3CSK4 stimulation in vitro. Laser confocal microscopy showed that common carp Trif colocalized with the Golgi apparatus. A luciferase reporter assay showed that carp Trif elicited the activity of ifn-1 and nf-κb through the C-terminal domain. Additionally, crystal violet staining and qPCR assays revealed that carp Trif inhibited the replication of SVCV in epithelioma papulosum cyprini (EPC) cells. Then the signaling downstream of carp Trif was investigated. Coimmunoprecipitation and western blotting analysis demonstrated that carp Trif interacted with TBK1 and augmented the expression of TRAF6 and phosphorylation of TBK1. Overexpression of carp Trif significantly enhanced the expression of interferon-stimulated genes and inflammatory cytokines. Furthermore, flow cytometric (FCM) analysis suggested carp Trif induced apoptosis through the activation of caspase-8. In summary, our study indicated that Trif plays an essential role in the innate immune responses of common carp against bacterial and viral infection.